Effect of polarization switching on piezoelectric and dielectric performance of electrospun nanofabrics of poly(vinylidene fluoride)/Ca–Al LDH nanocomposite. Issue 20 (8th November 2019) - Shamitha, C.; Mahendran, Arunjunairaj; Anandhan, S.
ABSTRACT: At present, highly flexible, durable, and lightweight piezoelectric nanogenerators with high‐power density and energy conversion efficiency are of great interest. The present study reports a new synthetic route for Ca–Al layered double hydroxide (LDH) nanosheets and incorporation of these two‐dimensional nanosheets as filler material into poly(vinylidene fluoride) (PVDF) to produce composite nanofabrics by electrospinning. The polymorphism, crystallinity, and the interaction between PVDF and LDH were studied by Fourier transform infrared spectroscopy, X‐ray diffraction, and differential scanning calorimetry techniques. The synergetic effect of PVDF–LDH interaction and in situ stretching due to electrospinning facilitates the nucleation of electroactive β phase up to 82.79%, which makes it a suitable material for piezoelectric‐based nanogenerators. The piezoelectric performance of PVDF/Ca–Al LDH composite nanofabrics was demonstrated by hand slapping and frequency‐dependent mechanical vibration mode, which delivered a maximum open circuit output voltage of 4.1 and 5.72 V, respectively. Moreover, the composite nanofabrics exhibited a high dielectric constant and low dielectric loss due to superior interfacial polarization at low‐frequency region with LDH loading, promising its potential applications in electronic devices. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 137, 48697. Abstract : Polarization switching of poly(vinylidene fluoride)/Ca‐Al LDH composite nanofabrics